1989
DOI: 10.1002/mus.880120508
|View full text |Cite
|
Sign up to set email alerts
|

The quadriceps femoris muscle in 20–70‐year‐old subjects: Relationship between knee extension torque, electrophysiological parameters, and muscle fiber characteristics

Abstract: Comparisons have been made between torque (isometric and isokinetic), electrophysiological (SFEMG, Macro EMG), and muscle fiber characteristics in the vastus lateralis muscle of both legs in healthy subjects aged between 20 and 70 years. Torque was greater in males and decreased with age in both sexes. Multifactorial analysis showed a positive correlation between torque, body surface area, and mean fiber area. These variables explained only about 30-40% of the torque changes. The electrophysiological parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 21 publications
4
57
0
2
Order By: Relevance
“…Isometric muscle strength loss was reported to begin at an earlier age, but at a slower rate, in women (64); thus, the percentage of loss would be less in women (65,66). Our data of a less-rapid decline in women are consistent with these results.…”
Section: Sex Differencessupporting
confidence: 82%
“…Isometric muscle strength loss was reported to begin at an earlier age, but at a slower rate, in women (64); thus, the percentage of loss would be less in women (65,66). Our data of a less-rapid decline in women are consistent with these results.…”
Section: Sex Differencessupporting
confidence: 82%
“…It should be emphasized that the relationships observed are relatively weak, and, therefore, that conclusions must be drawn from the present study with caution. The weak correlations are not surprising in view of the fact that other factors are also likely to determine medical consumption, and that the measurement of muscle strength usually has important interindividual variability [27,28]. Psychosocial factors may also be related to the utilization of health care resources.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, advancing age leads to deficits in the processing of sensory input (myelin abnormalities, axonal atrophy, and declined nerve conduction velocity) [7,24,59,74] and neuromuscular performance decline. It has been shown that the older adult has fewer, but on average larger and slower motor units, resulting in motor unit reorganization [9,14,40,65,66]. Therefore, this age-related alteration of the number and function of motor units have profound implications in muscle force production and control.…”
Section: Mechanisms Of Proprioception Deterioration With Agingmentioning
confidence: 99%